2007
DOI: 10.1111/j.1365-2427.2007.01821.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleuston communities are buffered from regional flood pulses: the example of ostracods in the Paraná River floodplain, Brazil

Abstract: 1. It is widely acknowledged that sudden, large-scale flood pulses are drivers of benthic and planktonic biodiversity change in floodplains. The impact of such pulses on pleuston (biotic communities associated with root systems of floating plants) remains to be demonstrated. Here, we investigate the effects of local and regional drivers on seasonal changes in abundance and diversity of ostracod communities in pleuston. 2. Temporal and spatial distribution patterns of species richness, abundance, diversity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 22 publications
3
55
0
4
Order By: Relevance
“…In this way, some authors have attributed the flood pulse as the main factor structuring the distinct aquatic communities in the Upper Paraná River floodplain (Lima et al, 1998;Bonecker et al, 2005). On the other hand, some studies have suggested that the spatial heterogeneity in floodplain systems, including the differences in the hydrodynamic and connectivity, is an important factor on the communities' organization, more than the temporal changes determined by the flood pulse (Velho et al, 2004;Higuti et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this way, some authors have attributed the flood pulse as the main factor structuring the distinct aquatic communities in the Upper Paraná River floodplain (Lima et al, 1998;Bonecker et al, 2005). On the other hand, some studies have suggested that the spatial heterogeneity in floodplain systems, including the differences in the hydrodynamic and connectivity, is an important factor on the communities' organization, more than the temporal changes determined by the flood pulse (Velho et al, 2004;Higuti et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also beta diversity was relatively low, as similarity in ostracod communities between the various lakes, rivers and channels was high. This is illustrated by the community of Manezinho, a relatively small backwater of the main Paraná River channel, where the pleuston (root systems) of Eichhornia crassipes (only one of several possible host plants) turned out to comprise 27 species, half the total gamma diversity of the entire alluvial valley (Higuti et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…benthos, phytoplankton, zooplankton, fish and/or macrophytes . However, Higuti et al (2007) argued that meiobenthic groups, such as ostracods, in pleuston (floating root systems) might actually be buffered from the putatively detrimental effects of sudden flood pulses, as floating plants will simply follow changing water levels with minimal changes in environmental conditions. Therefore, flood pulses are expected to mainly affect benthic habitats (including the littoral), and the fact that most habitats in the present study are indeed floating plants might explain the lower relevance of the regional factor 'system'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os crustáceos de água doce, cladóceros e copépodos têm sido relativamente bem explorados em nosso país, tanto em termos ecológicos como em estudos sobre taxonomia. Por outro lado, a despeito de os ostrácodes serem abundantes na maioria dos corpos de água, ainda existem poucos estudos em ambientes aquáticos continentais brasileiros (Würdig & Freitas, 1988;Higuti, 2006;Higuti et al, 2007Higuti et al, , 2009bHiguti et al, , 2010Miranda, 2008;Mormul et al, 2010;Pereira, 2010;Matsuda, 2011;Chaves 2012;Matsuda et al 2015a,b;Higuti & Martens, 2016).…”
Section: Methodsunclassified